Skin deep: Cutaneous manifestation of PIP implant rupture - Casey, Máire-Caitlín (JPRAS Open, 2021)
PIP (Poly Implant Prothèse, France) implants were readily employed for breast reconstruction until withdrawn from the market in 2010. These implants have an early and increased risk of rupture compared to non-PIP implants. This report outlines a significant cutaneous manifestation of PIP-implant rupture not previously described in the literature. This patient developed significant cutaneous xanthomatous inflammation with sinus tract formation that has yet to resolve despite explantation. Further investigation is warranted to elucidate the aetiology of this clinical sign and the optimal management of the cutaneous manifestation.